Factors controlling the geometry of travertine mounds: Insights from Heinitang (China). Issue 4 (21st December 2021) - Luo, Lianchao; Wen, Huaguo; Brogi, Andrea; Capezzuoli, Enrico
Abstract: Travertine mounds are common spring‐constructed landforms with highly variable geometries, but factors controlling their development have not yet been fully understood. To investigate processes linked with their lateral and vertical growth, this study investigated travertine mounds at Heinitang (China) and compared them with typical mounds around the world. Calcium concentration variation modelling and height evaluation of travertine mounds were also performed. The lateral extent of travertine mounds was found to be mainly controlled by Ca 2+ and HCO 3 ‐ concentrations and water discharge: relatively small metre‐scale mounds, like those from Heinitang, are largely the products of Ca 2+ ‐deficiency (<150 mg L −1, commonly <100 mg L −1 ) or HCO 3 ‐ ‐deficiency (<500 mg L −1 ) springs with low discharges (<0.1 L s −1 ), whereas springs with higher Ca 2+ and HCO 3 ‐ concentrations and discharges give rise to the formation of wider mounds. Additional factors affecting mound lateral development include infiltration, evaporation, micro‐organisms, water cooling, CO2 degassing and flow paths. Height of travertine mounds cannot be simply considered to represent the piezometric surface, because the vertical growth of travertine mounds is also influenced by the water table change triggered by tectonic pulses and climate fluctuations, and the closing of conduits induced by self‐sealing. The extinction of travertine mounds at Heinitang is, for example, probably caused by the water table lowering triggered by earthquakes or climate drying after 4 kyr bp . These findings offer new inputs for the better understanding of factors controlling travertine mound development and might assist in the reconstruction of fluid properties, hydrodynamics, tectonics and climate fluctuations in fossil geothermal systems with travertine mounds.